Metastasis And Metastability A Deleuzian Approach to Information - Faucher, Kane X.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
The word (3z(Binformation(3y (Bcarries a number of connotations depending on context, and can be said to be one of the most problematic words to define despite many efforts by statistical theorists, mathematicians, physicists, cyberneticians, communication theorists, computer scientists, and philosophers. Is information physical or non-physical? Is the universe digital, analog, or a (3z(Bchaosmic(3y (Bmixture of the two? This book explores a Deleuzian way of understanding information by retracing Deleuze$1 (Bs ontology of difference back to Gilbert Simondon$1 (Bs concepts of transduction, metastability, and perpetual individuation as a source for Deleuze$1 (Bs concept of the virtual. Although Deleuze did not address information specifically in his oeuvre, this book attempts to construct what a Deleuzian theory of information might look like as a consequence of his philosophical insights. The reader is presented with a brief survey of information theories, capsule explanations of the philosophy of Gilbert Simondon and Gilles Deleuze, and a discussion on the roles of metastasis and metastability as a means of addressing the problematic known as information outside of computing regimes, and as a critique of cybernetics, informatics, and memetics. Can information be reconfigured as affirmative difference, transformed into a (3z(Bnomad science,(3y (Bor must it remain consigned to the realm of probabilism?s
Keywords: Education; Education; Education (general).